2022
DOI: 10.52547/pbp.4.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aju Mbaise on sperm morphology, semen quality, sex hormonal levels, gonadosomatic index and testicular histology of Avodart-induced rats

Abstract: Objective: This study evaluated the effect of ethanol extract of Aju Mbaise (EEAM) on sperm morphology, semen quality, sex hormonal levels, gonadosomatic index and testicular histology of Avodart-induced rats. Material and Methods:The study had normal control, Avodart control, EEAM control, Avodart+500mg/kg EEAM, and Avodart +1000mg/kg EEAM groups. The rats were orally administered 0.5 mg/kg Avodart and 1 hour later treated with EEAM for 28 consecutive days. The Avodart control had milky white semen with low P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…These findings suggest that raised doses of ABE might have induced synthesis of these antioxidant enzymes or stabilized the amount of the circulating enzymes which could have prevented oxidative stress-induced damage and complications in the diabetes-induced rats administered 400, and 800 mg/kg ABE respectively. The significant rise in the GSH, CAT, GPx, and SOD activities in the diabetic rats administered ABE is consistent with the findings of Sarfraz et al, (2017) (Sarfraz et al, 2017) and Uroko et al (2022b) (Uroko et al, 2023) that medicinal plant extract with antioxidant property prevents oxidative stress and lipid peroxidation by promoting the induction of antioxidant enzymes and stabilization of the circulating antioxidants.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings suggest that raised doses of ABE might have induced synthesis of these antioxidant enzymes or stabilized the amount of the circulating enzymes which could have prevented oxidative stress-induced damage and complications in the diabetes-induced rats administered 400, and 800 mg/kg ABE respectively. The significant rise in the GSH, CAT, GPx, and SOD activities in the diabetic rats administered ABE is consistent with the findings of Sarfraz et al, (2017) (Sarfraz et al, 2017) and Uroko et al (2022b) (Uroko et al, 2023) that medicinal plant extract with antioxidant property prevents oxidative stress and lipid peroxidation by promoting the induction of antioxidant enzymes and stabilization of the circulating antioxidants.…”
Section: Discussionsupporting
confidence: 89%
“…The significantly higher levels of malondialdehyde (MDA) in the diabetic rats that were untreated in comparison with the normal control indicated increased levels of lipid peroxidation and oxidative stress associated the diabetes progression in the diabetic untreated rats which align with the findings of Ashor et al (2016) (Ashor et al, 2016). Contrarily, the significant decline in the diabetic rats administered 200mg/kg, 400mg/kg, and 800 mg/kg ABE respectively relative to the diabetic untreated rats indicated that treatment of diabetic rats with ABE could substantially prevent lipid peroxidation and its associated adverse health consequences in line the findings of Uroko et al (2022b) (Uroko et al, 2023).…”
Section: Discussionsupporting
confidence: 85%
“…However, the sensitivity of sports-related brain imaging ndings is not su cient for diagnosis due to a large amount of diversity in the neuropathological changes caused by TBI and the interindividual variability in severity. 7 In addition, in some contact sports, there are no substantial structural abnormalities on MRI. 8,9 Therefore, it may be suggested that consistent ndings related to rmTBI are not fully available.…”
Section: Introductionmentioning
confidence: 99%